Synthesis of 7-alkylidene-7, 12-dihydroindolo[3, 2-d]benzazepine-6-(5H)-ones (7-alkylidene-paullones) by N-cyclization–oxidative Heck cascade and characterization as sirtuin modulators1. Issue 9 (7th March 2015) - Denis, J. G.; Franci, G.; Altucci, L.; Aurrecoechea, J. M.; de Lera, Á. R.; Álvarez, R.
<x xml:space="preserve">Abstract</x> A palladium-induced cascade of N-cyclization and oxidative Heck reaction of o-alkynylanilines produced 7-alkylidene-indolobenzazepinones (paullones) that have sirtuin modulation activities.